Developing picture storybooks assisted by word search puzzle to improve elementary students’ indonesian vocabulary mastery - Andhini Pramudita; Nugraheti Sismulyasih SB (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study presents the low reading comprehension of elementary students associated with limited vocabulary mastery. It aims to develop picture storybooks assisted by a word search puzzle and examine their feasibility and the tendency of vocabulary improvement after implementation. The study employed a Research and Development (R&D) design based on Borg & Gall’s model, adapted into eight stages. The participants were 30 fourth-grade students of SDN Jatilor Grobogan, including a small-scale trial (6 students) and a usage trial (24 students). Data were collected through observation, interviews, questionnaires, and pre-test–post-test using valid and reliable instruments. Product feasibility was evaluated by a media expert, a material expert, a teacher, and students. Meanwhile, effectiveness testing employed a one-group pre-test–post-test design, and was analyzed using a paired-sample t-test and N-Gain. The results indicated that the product was highly feasible, with scores above 90%. Statistical analysis showed a significant difference between pre-test and post-test scores (p < 0.05), with mean scores increasing from 63.75 to 80.83 and an N-Gain of 47,11% (moderate category). These findings indicate an improvement in vocabulary mastery following implementation, although these should be interpreted with caution due to the absence of a control group.